Infinite exchange: The social ontology of the photographic image. (1st March 2010) - Osborne, Peter
This paper approaches the problem of the ontology of the photographic image post-digitalization historically, via a conception of photography as the historical totality of photographic forms. It argues, first, that photography is not best understood as a particular art or medium, but rather in terms of the form of the image it produces; second, that the photographic image is the main social form of the digital image (the current historically dominant form of the image in general); and third, that there is no fundamental ontological distinction regarding indexicality between photographically generated digital images and those of chemically based photography. The anxiety about the real produced by digital imagery has its origins elsewhere, in the ontological peculiarities of the social form of value in societies based on relations of exchange. Distinguishing between the event of capture and the event of visualization, it is argued that it is in its potential for an infinite multiplication of visualizations that the distinctiveness of the digital image lies. In the digital image, the infinite possibilities for social exchange generated by the abstraction of value from use finds an equivalent visual form.